Water reports N.13 - FAO (FAO, 1997)
The publication is interest for use by planners, irrigation and drainage engineers and environmental specialists. It would be useful in project indentification and to assess potential adverse water quality impacts of drainage disposal practices and indentify alternative mitigation tchnologies. In addition, monitoring programmes to collect desired information are suggested.